2022
DOI: 10.47572/muskutd.1113136
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Mediastinal Schwannoma: with Two Case Reports

Abstract: ABSTRACT: The most common tumors in the posterior mediastinum are neurogenic tumors. Schwannomas are common among these tumors, which usually originate from the peripheral nerve sheath. Posterior mediastinal masses are mostly benign and have a good prognosis. Two cases who were operated for intrathoracic and paravertebral schwannoma in our clinic were evaluated in the light of the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
(1 reference statement)
0
0
0
Order By: Relevance
“…Schwannomas are benign nerve sheath tumors that should be considered and taken into account in radiological evaluation, particularly in cases of mediastinum diseases 5 . In our case report, we present a case diagnosed with Schwannoma who presented with complaints of sore throat and cough and underwent surgery due to a mass appearance on chest radiography.…”
Section: Figure 1 Chest Radiographymentioning
confidence: 99%
See 1 more Smart Citation
“…Schwannomas are benign nerve sheath tumors that should be considered and taken into account in radiological evaluation, particularly in cases of mediastinum diseases 5 . In our case report, we present a case diagnosed with Schwannoma who presented with complaints of sore throat and cough and underwent surgery due to a mass appearance on chest radiography.…”
Section: Figure 1 Chest Radiographymentioning
confidence: 99%
“…Schwannomas are the most prevalent neurogenic tumors in the mediastinum, especially in the posterior mediastinum. Schwannomas are a common type of tumor that arises from the peripheral nerve sheath [4][5][6][7] . In a single-center 10-year retrospective study, dermal and subcutaneous Schwannomas were found to be the most common (75.3%), followed by mediastinal Schwannomas (10.9%) 8 .…”
Section: Figure 1 Chest Radiographymentioning
confidence: 99%